Beyond-the-Standard Model Higgs Physics using the ATLAS Experiment - Truong Loan (EPJ Web of Conferences, 2016)
Recent searches for the Higgs boson in the context of beyond the Standard Model performed by the ATLAS experiment are presented: high mass Higgs boson searches, lepton flavour violating Higgs decay, NMSSM, constraint from the search for three photons. The interpretation based on the measurements of Higgs couplings is shown, along with the constraint on the Higgs boson invisible decays. The search for invisible decays of a Higgs boson produced in association with a Z boson was performed with both √s = 7 and 8 TeV while the rest were performed using the √s = 8 TeV data of proton-proton collisions collected by the ATLAS experiment. No significant excess of data over the predicted background is observed and limits are placed in certain quantities depending on the searches.